PENGARUH SUBTITUSI TEPUNG IKAN DENGAN TEPUNG Indigofera zollingerina TERHADAP PERTUMBUHAN IKAN GABUS (Channa striata) - Lestari, Siti; Puteri, Rizki Eka; Prariska, Donny; Sari, Selly Ratna; Guttifera, Guttifera (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
Snakehead (Channa striata) is a type of fish that has potential to be developed. In some areas in Indonesia, especially South Sumatra, this fish is a raw material for making local food which is in very high demand. However, the process of cultivating snakehead often experiences several obstacles that make it difficult for this fish to develop, one of which is the availability of feed. So that alternative feed ingredients are needed for the manufacture of feed so that it can reduce the cost of fish farming production. This study aims to determine the best percentage of Indigofera zollingerina substitution on the growth of snakehead (Channa striata). The research design used a completely randomized design (CRD) method with 4 treatments of fish meal substitution with Indigofera zollingerina 0%, 15%, 30% and 45%. Protein substitution of Indigofera zollingerina with different was best at 30% treatment and gave significantly different results on absolute weight growth and fish body length growth. However, it has no significant effect on the survival of snakehead. The best results were on absolute weight growth of 0.45 g, growth of snakehead body length of 4.77 cm and survival of snakehead of 98.89%.